Universities as local knowledge hubs under different technology regimes - New evidence from academic patenting - Friedrich Dornbusch; Thomas Brenner (Philipps-University Marburg, Department of Geography, 2013)
It is often claimed that universities act as local knowledge factories. Although this function is largely analyzed in previous research, there still is a knowledge gap regarding the role of a technological match between the profiles of partners in university-industry interactions. In addition, the effects of different knowledge dynamics in technological regimes remain under-researched. In this paper, we thus draw special attention to the question how geographical distance and the specific role of a technological fit between the knowledge provided by the university and the technological needs of the local industry affects interactions between universities and firms. Thereby, we differentiate between six technological regimes constituted by different knowledge dynamics. Our analyses are based on a unique dataset containing all German universities' academic patenting and publication activities. As these are further enriched by secondary data, they enable us to show that the technological fit between a university and its surrounding region (in terms of local industry needs) indeed has a significant influence on a university's innovation-related research interactions, especially with small firms. We further show that this effect additionally depends on the underlying knowledge base in heterogeneous technological regimes.
Keywords: O31; R12; L14; 330; university-industry interaction; technological fit; knowledge base; academic patenting; technology regime; local knowledge hub